ROLE OF MRI BRAIN IN POSTPARTUM CONVULSIONS - fatima Imran; Zonia zaman (Journal of University Medical & Dental College, 2017)
Abstract: Objective: To assess the role of brain magnetic resonance imaging in evaluation of the causes of postpartum convulsions. Setting and Duration of Study: This cross sectional study was conducted in Department of Radiology and Obstetrics & Gynecology, Aziz Fatimah Trust Hospital and Medical and Dental College Faisalabad, from April 2015 to March, 2016 in a period of one year. Methodology: All the women visiting to the OPD or admitted for postpartum seizers having age from 23 to 38 years, delivered after a term pregnancy were included in the study. Brief history of hypertension and any other comorbid disease was taken. All the patients fulfilling inclusion criteria based on clinical assessment and obstetric history were referred for brain MRI in the radiology department. Supine position was used to execute MRI examination in all patients. Head coil was used to get images in axial, sagittal and coronal planes in whole study sample. Results: The mean age was noted to be 29.77 ± 2.380 years. There were 43 (78.18%) patients who were ≤ 30 years old. The mean gestational age in this study was 37.40 ± 0.875 weeks and 44 (80.0%) were nulliparous. MRI scan of the brain was observed positive in 32 (58.18%) women and 23 (41.82%) had negative MRI findings. Among the women having positive MRI the commonest finding in 15 (46.88%) patients was Dural sinus thrombosis followed by Posterior reversible encephalopathy in 8 (25%) patients and Intra cerebral hemorrhage was observed in 5 (15.63%) patients. Subarachnoid hemorrhage was noted in 3 (9.38%) and pituitary apoplexy was found in 1 (3.13%) patient. Conclusions: There are several causes of seizures in the post-partum period like dural sinus thrombosis was found in (46.88%) patients followed by Posterior reversible encephalopathy (25%) and Intra cerebral hemorrhage was observed in (15.63%) patients. Early diagnosis of the cause of postpartum seizers on the basis of brain MRI will help in proper management of the patient and avoiding damaging complications or permanent neurologic damage.